Flat but expressive? On the construction mechanisms of punchlines in flat jokes - Wowro, Iwona (Papers in Linguistics, 2026)
As a cultural construct and a filter for perceiving reality, humour assumes various functions and forms present in different situations and social attitudes. A joke constitutes a basic unit of comedy, with its key element being a punchline, bringing the effect of surprise and determining the reception of the entire text. The basis of comedic effect lies in noticing inconsistencies within the structure or content of a comedic act. One form of humour is the so called flat joke, which is relatively rarely discussed in academic literature and often overlooked in scientific studies. A flat joke is characterized by a simple structure, predictability, and deliberate use of triviality, which can provoke both laughter and embarrassment, sometimes creating a sense of distance from the teller. The aim of this article is to examine the nature of flat jokes, as based on selected material, and above all to identify the most common techniques and mechanisms for constructing punchlines. The article will present different types of punchlines and linguistic devices used to build them, such as wordplay, conciseness, meaning shifts, and sudden perspective changes, which shall make it possible to better understand the specificity of the analysed category of jokes.